Effective refolding of a cysteine rich glycoside hydrolase family 19 recombinant chitinase from Streptomyces griseus by reverse dilution and affinity chromatography - Oyeleye, Ayokunmi Omolola; Mohd Yusoff, Siti Faridah; Abd Rahim, Izzah Nadiah; Thean, Adam Chor Leow; Saidi, Noor Baity; Mohd Yahaya, Normi (Public Library of Science, 2020)
Conventional refolding methods are associated with low yields due to misfolding and high aggregation rates or very dilute proteins. In this study, we describe the optimization of the conventional methods of reverse dilution and affinity chromatography for obtaining high yields of a cysteine rich recombinant glycoside hydrolase family 19 chitinase from Streptomyces griseus HUT6037 (SgChiC). SgChiC is a potential biocontrol agent and a reference enzyme in the study and development of chitinases for various applications. The overexpression of SgChiC was previously achieved by periplasmic localization from where it was extracted by osmotic shock and then purified by hydroxyapatite column chromatography. In the present study, the successful refolding and recovery of recombinant SgChiC (r-SgChiC) from inclusion bodies (IB) by reverse dilution and column chromatography methods is respectively described. Approximately 8 mg of r-SgChiC was obtained from each method with specific activities of 28 and 52 U/mg respectively. These yields are comparable to that obtained from a 1 L culture volume of the same protein isolated from the periplasmic space of E. coli BL21 (DE3) as described in previous studies. The higher yields obtained are attributed to the successful suppression of aggregation by a stepwise reduction of denaturant from high, to intermediate, and finally to low concentrations. These methods are straight forward, requiring the use of fewer refolding agents compared with previously described refolding methods. They can be applied to the refolding of other cysteine rich proteins expressed as inclusion bodies to obtain high yields of actively folded proteins. This is the first report on the recovery of actively folded SgChiC from inclusion bodies.